CRIMINAL STUDY ON ERADICATION OF LAND MAFIA IN NORTH SUMATRA PROVINCE - Hermanto, Dimas; Ramadhani, Rahmat (Inspiring Law Journal, 2024)
The land mafia is a nefarious alliance practice that flourishes due to low public scrutiny and lack of law enforcement. Modus the land mafia's modus operandi includes conspiring with the agency that issues the title deeds, fabricating cases, and pretending to conduct sale and purchase transactions. Evidence of rights, fabricating cases, and pretending to conduct sale and purchase transactions. The Constitution of the Republic of Indonesia at the beginning of the formation of the country's foundation has been regulated regarding land, this can be seen in the provisions of Article 33 paragraph (3) of the 1945 Constitution which has 1945 which has rescued the state that everything related to land as part of the earth, water to land as part of the earth, water and natural resources contained therein in Indonesia must and contained therein in Indonesia must and must be managed and utilized for the greatest prosperity.utilized for the greatest prosperity of the Indonesian people. The research used is a type of empirical legal research or called field research, namely examining the applicable legal provisions and what happens in reality in society. What happens in reality in society in this study approach used in solving the problem is to use statute approach. The results showed that in handling land mafia cases, The National Land Agency expressly established the Technical Guidelines for the Prevention of Land Mafia Eradication Number: 01/JUKNIS/D.VII/2018 on the Prevention and Eradication of the Land Mafia. In the implementation point based on the technical guidelines, the prevention of land mafia is carried out by the establishment of a Task Force for the Prevention and Eradication of the Land Mafia, both at the Ministry level, Regional Office level and Land Office level, and socialization of land mafia prevention and eradication and socialization